IDENTIFICATION OF DERMATOPHITE FUNGI ( TINEA UNGUIUM ) ON NAIL SCREENING OF CHICKEN TRADERS IN PANORAMA MARKET, BENGKULU CITY IN 2021 - Putri Widelia Welkriana; Apriansyah Saputra; Susiwati Susiwati (Avicenna: Jurnal Ilmiah, 2021)
Background : Chicken traders work using both hands to clean and cut chickens. With conditions due to their lifestyle which always struggles with damp and wet triggers the emergence of skin diseases, one of which is Tinea Unguium which is caused by fungi, especially Trichophytonrubrum. Objective: The purpose of this study was to determine the presence or absence of Tinea Unguium fungus in Nail Scrapings of Chicken Traders and to determine macroscopically the condition of Chicken Traders' nails at Panorama Market, Bengkulu City. Methods: This research is descriptive observational research by testing the sample. A total of 23 samples were taken directly by scraping the nails of chicken traders. Results: Based on the results of the research, the sample of nail scrapings from chicken traders was that most of the respondents were not infected with Tinea Unguium fungus, as many as 14 respondents, 60.9%, and almost half were infected with Tinea Unguium fungus, as many as 9 respondents, 39.1%.Macroscopically from 9 traders who were infected with Tinea Unguium fungus, there were 6 traders who had clinical symptoms and 3 other traders had normal nail conditions or did not have clinical symptoms. Conclusion: concluded that The results of this studyhalf of the respondents were not infected with the fungus Tinea Purple and a small proportion of respondents were infected with the fungus Tinea Purple.Suggestion: As knowledge for the community and academics so that it becomes a reference for further research that is more varied.